Engineering teacher's guide - Lloyd Ch. Charles (Career Paths)
Career Paths: Engineering is a new educational resource for engineering professionals who want to improve their English communication skills in a work environment. Incorporating career-specific vocabulary and contexts and reviewed by leaders within the engineering industry, each unit offers step-by-step instruction that immerses students in the four key language components: reading, listening, speaking, and writing. Career Paths: Engineering addresses topics including tools, materials, numbers, engineering concepts, converting measurements, and career options. The series is organized into three levels of difficulty and offers over 400 vocabulary terms and phrases. Every unit includes a test of reading comprehension, vocabulary, and listening skills, and leads students through written and oral production. Included Features: a variety of realistic ;reading passages ; Career-specific dialogues ; 45 reading and listening comprehension checks ; Over 400 vocabulary terms and phrases ; Guided speaking and writing exercises ; Complete glossary of terms and phrases. The Teacher's Guide contains detailed lesson plans, a full answer key and audio scripts. The audio CDs contain all recorded material.